THE INFLUENCE OF PRODUCT QUALITY, BRAND IMAGE AND PRODUCT DESIGN ON THE DECISION TO PURCHASE AN IPHONE (Case Study of Fdstore Customers in Tebing Tinggi City) - Benhart Nainggolan; Suwadi (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
This research aims to determine the influence of product quality, brand image and product design on iPhone purchasing decisions (case study of customers of the Fdstore store in Tebing Tinggi City). The research method used is a quantitative method using SPSS version 25.00. The technique for determining the sample size used a total sampling of 56 respondents, namely consumers who bought iPhones at the Fdstore shop in Tebing Tinggi City. The sampling technique for this research uses accidental sampling. The analytical method used in this research is multiple linear regression analysis and hypothesis testing. The results of this research are 1) product quality influences purchasing decisions, 2) brand image influences purchasing decisions, 3) product design influences purchasing decisions, 4) product quality, brand image and product design simultaneously influence purchasing decisions.